Pleasure Reading Habits of Library Users at the Main Library of University of Colombo - Perera, K.K.N.L.; Somaratna, Sajeewanie D. (ULA, 2016)
Pleasure reading refers to free, voluntary and non-goal oriented reading which provides enjoyment or a pleasure to the reader. Since pleasure reading exert significant, positive impacts on the overall performance of academic library users, a study was carried out to explore the pleasure reading habits of users and their perceptions on the benefits of pleasure reading, at the Main Library of University of Colombo.209pleasure readerswere identified, over a period of one month. The sample consisted of; undergraduates who borrow pleasure reading materials over the counter, undergraduates who search for pleasure reading materials and undergraduates who readfor pleasureat the Main Library premisses. It was found that the Main Library possesses a significant population of pleasure readers with diverse reading habits. A majority of pleasure readers are frequent readers. Their reading frequency differed over gender.‘Novels’ are the most popular type of reading materials followed by ‘Non-fictions’ and ‘Short stories’.‘Realistic fiction’ is the most popular genre, followed by fantasy and Mystery.Three benefits of pleasure reading were highly popular among pleasure readers. They were;pleasure reading helps to relax; it gives enjoyment; and helps to escape from routine work. A majority of pleasure readers believe that promotion of pleasure reading must be a priority of an academic library. This study created a necessity of carrying out future research on user perceptions, expectations and promotional activities related to pleasure reading at academic libraries in Sri Lanka.
Keywords: Pleasure reading, Academic libraries, Pleasure reading habits, Benefits of Pleasure reading, User perception